DEVELOPMENT DEVELOPMENT OF ANIMATION VIDEO MEDIA FOR IPS LEARNING MATERIALS GLOBALIZATION - Mhd Faisal Raya Hasibuan; Hidayat (Jurnal Pendidikan LLDIKTI Wilayah 1 (JUDIK), 2021)
Mhd Faisal Raya Hasibuan, 171434266, ''Development of Animated Video Media for Social Studies Learning Globalization Materials'' This study aims to determine the feasibility of animated video media in social studies learning material for Globalization. This research was conducted at the Library of UMN Al Washliyah Medan. The method use dis the development of research methods 4-D, which consist soft 4 stages which define (definition) , design (planning), development (development) and disseminate (spread). Animated videos were validated by two experts, namely material experts and media experts. Furthermore, product trials were carried out to material experts and media experts. The results of the validation test of the experts received an assessment with a decent category. Based on the results of the study, Keywords: learning media, social studies, animated videos.